PEDAGOGICAL FACILITATION IN TEACHING ENGLISH - Otakulova N. Kh.; Yusupova Sh.A. (Academia Science Repository, 2023)
A teaching strategy known as pedagogy involves professors instructing students both in theory and in practice. Pedagogy is influenced by educators' teaching philosophies and includes their knowledge of cultural differences and various learning styles. In order to consolidate earlier knowledge, it is crucial for students to create meaningful classroom interactions. Pedagogy is the study of how to teach pupils, whether through theory or in the classroom. There is a connection between learning methods and cultural practices. Building on the knowledge pupils have already acquired, pedagogy works to help students enhance their abilities and attitudes. The use of pedagogy helps students study a subject thoroughly and applies what they have learned in real-world situations outside of the classroom.